Pengaruh Financial Development, Investasi Asing Langsung dan Urbanisasi Terhadap Ketimpangan Pendapatan di Indonesia - Fajar Hendito Restulillah; Ariusni Ariusni (Universitas Negeri Padang, 2020)
This study aims to determine the effect of financial development on income inequality in Indonesia. The influence between foreign direct investment and income inequality in Indonesia. The influence between urbanization and income inequality in Indonesia. The data in this study uses secondary data from 1981 to 2018 obtained from the BPS and World Bank websites. This study uses multiple linear regression models. As well as data analysis used, namely descriptive analysis and inductive, in inductive analysis there are several tests in it including: (1) Ordinary Least Squares (OLS) test, (2) Classical Assumption Test (3) Error Correction Model (ECM)(4) Final results of long-term equations, (5) Hypothesis Test. The results of this study found that in the long-term financial development has a significant positive effect, foreign direct investment has a significant negative effect and urbanization has a positive and significant effect on income inequality in Indonesia. Meanwhile, in the short-term financial development has a positive and insignificant effect, foreign direct investment has no significant positive effect and urbanization has a negative and insignificant effect on income inequality in Indonesia.